Access of children to the oral health service - Moimaz, S. A. S. [UNESP]; Saliba, O.; Lima, D. P.; Joaquim, R. C.; Rovida, T. A. S.; Garbin, C. A. S. (Oral Health And Dental Management, 2014)
Dental caries still affect a considerable proportion of children, however the epidemiological profile of oral diseases is changing, social inequalities cause different disease patterns. The same problems occur for the use of services, which damage those who are more susceptible to oral diseases in numerous ways. To verify the association between the variables: socioeconomic condition, oral health and access to dental services providing oral health care for preschool children. The study population consisted of 2,759 children up to 6 years-old. The clinical exams followed the World Health Organization (WHO) criteria. The data were collected using a self-applied questionnaire, answered by the carers of children, with questions about socioeconomic variables and access to dental services. In terms of social class, a majority of the subjects came from the middle socioeconomic level (babies, 84.7%; children, 82.8%). Babies who had caries, 48.4% and 67.2% of the children that had decayed teeth had access to dental service. There was a association between the variables: the reason for the last dental appointment and the parent's perception of the treatment need of their children (babies p=0.0004 and children p < 0.0001); the parent's perception of the treatment need of their children and the oral health condition (babies p=0.0008 and children p < 0.0001); access to dental services and oral health condition (babies p=0.0021 and children p < 0.0001). The majority of the population studied sought care from public dental service and was from the middle class.